Infrastructural development of smart cities as the background of digital transformation of territorial units - Gryshchenko, Iryna; Kruhlov, Vitalii; Lypchuk, Oksana; Lomaka, Ivanna; Kobets, Yuliia (University of Zulia, 2022)
The Interoperability, continuous data and technology flw are core requirements of a proper smart city. Smart cities take on the characteristics of innovative, competitive and attractive megalopolises, which is strategically important for residents and investors. The aim of the article was to identify the current state and current issues of the Smart City concept implementation in Ukraine in the context of the experience of developed countries. The main methodological tools included the observation, statistical and comparative analysis. The study found that the effctive development of digital transformation of territorial units in Ukraine requires focusing on certain factors during the implementation of the Smart City concept. Such factors conditionally include: technology-based infrastructure; environmental comments; constructive level of public transport; progressive city plans; opportunities for citizens to use appropriate resources. It was found reasonable to introduce infrastructural development of smart cities in Ukraine as a foundation of digital transformation of territorial units. Smart Infrastructural Development of Smart Cities as the Background of Digital Transformation of Territorial Units Cities were substantiated as an important tool for effctive prevention and control of the pandemic without the introduction of restriction policies. A comparative analysis of the practice of Ukraine and developed countries in the implementation of infrastructural development of Smart Cities is a promising area of further research.
Keywords: cybersecurity; digitalization; innovative technologies; internet of Things; smart city